ANALYSIS OF CHEMICAL COMPOSITION OF DENTAL IMPLANTS - Grigorenko, A.Ya.; Kremenitsky, V.V.; Los, V.V.; Malanchuk, V.O.; Sorochenko, G.V.; Sperkach, S.О.; Tormakhov, М.М. (Reports of the National Academy of Sciences of Ukraine, 2023)
The qualitative and quantitative chemical composition of dental implants and the topography of their surfaces were examined using X-ray microanalysis with an X-ray microanalyzer (JXA-8200) and a scanning electron microscope (JSM-6490LV) manufactured by Jeol Ltd (Japan). The surfaces of the flat part of the cutting groove and the surfaces of the tip and the grooves of both large and small dental implant threads were investigated. The chemical composition of dental implant surfaces was found to be heterogeneous. In most cases, implant surfaces had undergone processing to increase surface roughness, clean the surface, passivate it, apply coatings with various materials to enhance its biological activity, and impart hydrophilic properties. These processes also aimed to enhance the microporosity of the implant structure.